2019
DOI: 10.1111/sjop.12543
|View full text |Cite
|
Sign up to set email alerts
|

From trust in caregivers’ support to exploration: The role of openness to negative affect and self‐regulation

Abstract: Attachment theory assumes that trust in caregivers’ support and exploration are closely related. Little research tried to investigate this link, nor focuses on mechanisms that might explain this association. The present studies examined whether trust is related to exploration through a serial indirect effect of openness to negative affect and self‐regulation. In Study 1, 212 children, aged 8–13, completed questionnaires assessing trust, openness to negative affect, self‐regulation and exploration. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
(118 reference statements)
1
2
0
Order By: Relevance
“…In Hornstein et al (2017) it was found that when a picture of an attachment figures was paired with a neutral stimulus during threat learning, fear acquisition for the neutral stimulus was inhibited as compared to fear acquisition with a neutral stimulus that had been paired with a picture of a stranger. This is also in line with attachment theory, as research suggests that secure attachment facilitates autonomous exploration of the environment, which can only be achieved if fear for potential threats get to some extent contained even when attachment figures are not physically present (Heylen et al, 2019).…”
Section: Introductionsupporting
confidence: 76%
“…In Hornstein et al (2017) it was found that when a picture of an attachment figures was paired with a neutral stimulus during threat learning, fear acquisition for the neutral stimulus was inhibited as compared to fear acquisition with a neutral stimulus that had been paired with a picture of a stranger. This is also in line with attachment theory, as research suggests that secure attachment facilitates autonomous exploration of the environment, which can only be achieved if fear for potential threats get to some extent contained even when attachment figures are not physically present (Heylen et al, 2019).…”
Section: Introductionsupporting
confidence: 76%
“…The teacher also invites children to ask questions about the theme of the project so that the child gets information and understands the project to be made. Bowlby (in Heylen et al, 2019) argued that children's repeated experiences with teacher support during proximity-seeking and exploration in trust about teacher availability and support or the belief that teacher will be available if needed. Trust fosters exploration because children who have trust in teacher support believe that when exploration leads to elevated levels of distress as a consequence of getting hurt, scared or sad, their teacher will be there for them to provide proximity and support.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Waters and Deane (1985) proposed that an infant's trust in his or her care provider was shown by his or her use of the care provider as a secure base, which allowed him or her to explore the environment (also see Heylen et al, 2019). Attachment theorists have proposed that securely attached children develop an IWM, which includes a sense of trust in others and positive thoughts regarding the intentions of other people's behaviours (see Cohn, 1990;Lieberman, 1977).…”
Section: Trust and Attachmentmentioning
confidence: 99%